P = -4
Entering the answer into the formula to "prove" it.
-4 + 6 +3(-4) = 1 + 3(-4) +1
-4 + 6 -12 = 1 -12 + 1
-10 = -10
2006-11-24 05:08:52
·
answer #1
·
answered by the_lipsiot 7
·
0⤊
0⤋
p + 6 + 3p = 1 + 3p + 1 subtract 3p from each side & combine like terms
p+6=2 subtract 6 from each side
p=-4
2006-11-24 05:08:46
·
answer #2
·
answered by yupchagee 7
·
0⤊
0⤋
p + 6 + 3p = 1 + 3p + 1
4p + 6 = 3p + 2
p + 6 = 2
p = -4
2006-11-24 05:07:37
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
P= -4
2006-11-24 05:06:32
·
answer #4
·
answered by Max 6
·
0⤊
0⤋
p+3p-3p = -6+1+1
p= -4
2006-11-24 05:04:28
·
answer #5
·
answered by silvs 5
·
0⤊
0⤋
p=-4
2006-11-24 05:17:01
·
answer #6
·
answered by ag_iitkgp 7
·
0⤊
0⤋
you ought to double distribue and combine like phrases. subsequently foil (first, outer, inner, final)? be specific you comprise negatives. 3p^2-3p-3p+3 or 3p^2-6p+3 9p^2+6p+9p+6 or 9p^2+15p+6
2016-12-17 15:34:54
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
-3
Yeah, Silv got it right... now what did I do wrong?
Oh, 6-2 now equals 4. Who would have known!
2006-11-24 05:04:41
·
answer #8
·
answered by Raylene G. 4
·
0⤊
0⤋
it would be 7p + 7
2006-11-24 05:03:59
·
answer #9
·
answered by jrtootsiepop 3
·
0⤊
0⤋